Supramolecular assemblies of polybenzimidazole and aromatic polycarboxylic acids with superior mechanical and H2/CO2 separation properties. Issue 20 (20th April 2022) - Hu, Leiqing; Bui, Vinh T.; Fan, Shouhong; Guo, Wenji; Pal, Sankhajit; Ding, Yifu; Lin, Haiqing
Abstract : Polybenzimidazole is doped with aromatic polycarboxylic acids to form supramolecular assemblies achieving strong size-sieving ability and thus high H2 /CO2 selectivity. Abstract : Aromatic polycarboxylic acids complex with imidazoles, forming supramolecular assemblies. Herein, we demonstrate that polybenzimidazole (PBI) can be augmented by aromatic polycarboxylic acids, including phthalic acid (PA), trimesic acid (TMA), and pyromellitic acid (PMA), and the resulting supramolecular assemblies exhibit attractive H2 /CO2 separation performance for precombustion carbon capture. The acid doping decreases the free volume and gas permeability but increases H2 /CO2 selectivity, which can be correlated with the molar ratio of the protons to PBI repeating units in the assemblies. Increasing the temperature decreases the H2 /CO2 selectivity because of weakened interactions. When challenged with model gas mixtures, a supramolecular assembly based on TMA shows H2 /CO2 separation properties superior to state-of-the-art materials and above Robeson's upper bound. This study elucidates the fruitful harnessing of dynamic non-covalent bonds to design robust and highly selective membranes for industrial gas separations.